POSTCOLONIAL TRANSLATION STUDIES: FOREIGNIZATION AND DOMESTICATION OF CULTURE-SPECIFIC ITEMS IN OF MICE AND MEN’S INDONESIAN TRANSLATED VERSIONS - Hafizha Fitriyantisyam; Aris Munandar (Rubikon : Journal of Transnational American Studies, 2021)
Resistance to Western Culture can be seen through translator’s strategy of translating novels. This research aims to analyze the translation of culture-specific items in Indonesian translated versions of Of Mice and Men, originally written by John Steinbeck. The selected translated versions belong to the work of Pramoedya Ananta Toer (2003) and Ariyantri E. Tarman (2017). The translations of culture-specific items are analyzed under Transnational American Studies paradigm to find out the dominant translation principle applied in both translated versions and the results are discussed from the perspective of postcolonial translation studies. From the data, it is found out that the domestication principle is more dominant than foreignization strategy. Analyzed from postcolonial translation studies, the tendency to use the domestication principle in translated novels show the efforts of the target culture to fight against Western culture as the source culture. Although both Indonesian versions of Of Mice and Men mostly apply the domestication principle, the recent translated version (T2) shows an increase in the use of foreignization principle in which English loanwords are frequently used. From a postcolonial translation studies’ perspective, it can be concluded that target culture is against Western culture; however, the signs of cultural imperialism, especially linguistic imperialism, have grown in the recent years.